2004
DOI: 10.1580/1080-6032(2004)15[202:soamsi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessment of Acute Mountain Sickness in Adolescents: A Pilot Study☆

Abstract: AMS is a common problem among adolescents. There are increasing numbers of adolescents traveling to high altitudes, and there appears to be a lack of information about the prevalence of AMS in this age group. Motivated adolescents seemed capable of self-monitoring for AMS using the Lake Louise questionnaire. Combined with an appropriate ascent profile and support, we feel this approach may contribute to safety in the mountains and merits further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 20 publications
1
30
1
Order By: Relevance
“…We found no significant difference in the incidence of AMS (defined as LLS >3, validated in adolescents3) between young people and adults on any day, supporting previous studies 4. The proportion of subjects reaching the summit was similar between the two groups, with 110/181 adults and 6/12 children summiting (p = 0.460).…”
supporting
confidence: 87%
“…We found no significant difference in the incidence of AMS (defined as LLS >3, validated in adolescents3) between young people and adults on any day, supporting previous studies 4. The proportion of subjects reaching the summit was similar between the two groups, with 110/181 adults and 6/12 children summiting (p = 0.460).…”
supporting
confidence: 87%
“…Due to battery limitations while trekking, measurements were restricted to once daily in the morning. Subjects completed a self-assessment diary twice daily to elucidate AMS symptomatology using the standardized Lake Louise scoring system (LLSS) (Imray et al, 2004). This comprises 4 graded responses (0 ϭ none, 3 ϭ severe) to 5 symptoms: headache, gastrointestinal symptoms, fatigue, dizziness, and difficult sleeping.…”
Section: Pupillometer Measurement Descriptionmentioning
confidence: 99%
“…While not designed for use in children, a recent pilot study of the LLSS suggested that teenagers (15 to 18 yr old) are capable of using the self-assessment tool to identify AMS symptoms (Imray et al, 2004). Most previous studies have suggested that children develop AMS at a rate similar to adults when ascending to comparable altitudes over similar time periods Pollard et al, 2001;Moraga et al, 2002;Yaron et al, 2002).…”
Section: Introductionmentioning
confidence: 99%